PENDEKATAN GESTALT BERBASIS ISLAM: STUDI KASUS KEGAGALAN MENIKAH - Muhammad Hadhar Ilman; Nurjannah Nurjannah (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2026)
Marital failure, especially caused by betrayal, can have a profound psychological impact. In Islam, accepting destiny and living life with patience and trust in Allah are essential elements for emotional healing. This article explores the use of Gestalt therapy within Islamic counseling to assist individuals experiencing trauma due to marital failure. The study focuses on a 22-year-old woman who faced marital failure due to her fiancé’s betrayal, employing a qualitative approach. The Gestalt approach, centered on self-awareness, personal responsibility, and the integration of spiritual values, helps clients understand and accept their experiences. The findings indicate that this combination effectively enhances self-awareness, accelerates emotional recovery, and strengthens the spiritual relationship with Allah SWT.